Processes of Community Economic Development in Phayao, Thailand - Serthpol, Nawin (Dhammathas Academic Journal, 2019)
The research objective is to study the processes of community economic development in Phayao province of Thailand. The qualitative research was conducted by in-depth interviewing with the 25 key informants as the individual and group. The interview guideline was tested by 3 experts and 10 assistants to conduct the data. The results were found that: processes of the community economic development include; 1) learning the problems, need and self-empowerment, 2) group development, through establishing, planning, operating, receiving benefits and group maintaining, 3) capitals mobilization though searching, producing, sharing, cooperating and supporting, 4) economic processes through production, consumption, service, distribution, saving and investment, 5) community learning through grouping, facing the problems, local wisdom informants, receiving the training and learning with the networks, 6) the creation of community networks through connecting and communication, making decisions for cooperation, planning, co-activities, capitals mobilization and request for supporting, 7) the promotion of community welfare through common, emergency and investment welfare.